Putting work in its place : a quiet revolution - Meiksins, Peter, 1953- (Collection on technology and work., 2002)
Most books on the subject of work focus on the increased amount of time Americans spend on the job. Peter Meiksins and Peter Whalley address the counter-trend, examining the difficult path traversed by people who choose to work less than the standard ...